Complaints and their Redressal : A Study on the Indian Banking System - Singh, Ajay; Singh, Ashutosh (Indian Journal of Finance, 2021)
With more and more people coming under the gamut of financial inclusion, banking transactions have increased manifold. Banks are also striving hard to introduce innovative deliverables to lure and retain their customers on one hand and to reduce cost and increase profit on the other hand. As the Indian banking sector is trying to match its technical and manpower capabilities to meet new challenges, complaints from customers are bound to increase. This has made customer happiness a major concern in the banking sector. Thus, the grievance redressal mechanism has become an important component of banking operations. Taking note of such a scenario, the Banking Ombudsman Scheme was brought to light by the Reserve Bank of India in the year 1995. This scheme acts as the grievance redressal mechanism at the highest level which is parallel to the Alternate Dispute Resolution Mechanism. An effort was made in this paper to analyze the efficacy of this scheme over the years. Various parameters were studied with the help of trend analysis to conclude the findings. Findings of 10-year data showed that this scheme worked effectively for the urban and metropolitan customers, but is yet to achieve the desired results for rural and semi-urban customers. Among the categories of banks, foreign banks were found to be doing good in keeping their customers satisfied. The analysis also concluded that mainly retail customers have used this scheme to resolve their issues.